2007
DOI: 10.1038/ismej.2007.31
|View full text |Cite
|
Sign up to set email alerts
|

The effects of subtherapeutic antibiotic use in farm animals on the proliferation and persistence of antibiotic resistance among soil bacteria

Abstract: The use of antibiotics at subtherapeutic concentrations for agricultural applications is believed to be an important factor in the proliferation of antibiotic-resistant bacteria. The goal of this study was to determine if the application of manure onto agricultural land would result in the proliferation of antibiotic resistance among soil bacteria. Chlortetracycline-resistant bacteria were enumerated and characterized from soils exposed to the manure of animals fed subtherapeutic concentrations of antibiotics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
216
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(229 citation statements)
references
References 36 publications
10
216
1
2
Order By: Relevance
“…However, land application of animal manure or sewage sludge does not universally increase ARGs in soils (Zhou et al, 2010) and this increase is not maintained long-term (Fahrenfeld et al, 2014). For instance, manure from three dairy farms did not increase cultivable chlortetracycline-resistant bacteria when land-applied to soil (Ghosh and LaPara, 2007). Also in a microcosm study, the relative abundance of tetAP, tetX, and tetO genes decreased over time, and fell below the initial levels of the control soils during the 60d experimental periods .…”
Section: Responses Of Args Abundance and Compositionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, land application of animal manure or sewage sludge does not universally increase ARGs in soils (Zhou et al, 2010) and this increase is not maintained long-term (Fahrenfeld et al, 2014). For instance, manure from three dairy farms did not increase cultivable chlortetracycline-resistant bacteria when land-applied to soil (Ghosh and LaPara, 2007). Also in a microcosm study, the relative abundance of tetAP, tetX, and tetO genes decreased over time, and fell below the initial levels of the control soils during the 60d experimental periods .…”
Section: Responses Of Args Abundance and Compositionmentioning
confidence: 98%
“…This phenomenon may be due, at least partly, to potential changes in soil microbial composition including the native soil antibiotic-resistant bacteria (ARB) after the application of chemical fertilizer (Forsberg et al, 2014). Although chemical fertilizer had some effects on soil ARGs, these effects, not surprisingly, are weaker when compared with sewage sludge or chicken manure, considering that manure is rich in ARGs and ARBs , Jiang et al, 2002Ghosh and LaPara, 2007) and most ARGs are discharged from the municipal wastewater treatment process in the form of sewage sludge (Munir et al, 2011). However, land application of animal manure or sewage sludge does not universally increase ARGs in soils (Zhou et al, 2010) and this increase is not maintained long-term (Fahrenfeld et al, 2014).…”
Section: Responses Of Args Abundance and Compositionmentioning
confidence: 99%
“…Amendment of soils with manure from antibiotic-treated animals has been frequently reported as an important route by which ARGs enter the environment and food system (Ghosh and LaPara 2007;Heuer et al 2008). However, recent studies suggested that high frequencies of ARGs (such as β-lactamases and tetracycline-resistance genes) are encountered in manure from dairy cows receiving no administration of veterinary antibiotics (Kyselkova et al 2013;Udikovic-Kolic et al 2014).…”
Section: Diversity and Abundance Of Args In Soil And Manure Samplesmentioning
confidence: 99%
“…Antibiotics are widely used in agriculture for treatments of sick animals, infectious disease prophylaxis and growth promotion, accounting for at least half of the antibiotics produced worldwide (Ghosh and LaPara 2007;Allen et al 2010;Hu, Zhou and Luo 2010). However, most of antibiotics are poorly absorbed by animals and a large proportion (30%-90%) of them can be excreted and dispersed into soils when manure is applied as fertilizer (Zhang and Zhang 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation